The reasons and problems for the renewed interest in natural gas and liquefied natural gas (LNG) world wide during the late 1980s and early 1990s - Abdui Majid, Zulkifli (Penerbit UTM Press, 1991)
lncrease in world's energy demand, energy security and environmental concern has given rise to a new perception of natural gas and LNG as a valuable source and future resource of energy for the world. Although these factor has renewed the interest of natural gas as a fuel there are a number of problems to be overcome in order to put the projects (especially LNG) on stream. This paper will discuss the reasons and problems for the renewed interest in natural gas and LNG world wide during the late 1980s and early 1990s.